(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The research aims to know the extent to which the principles of governance are applied to the accounting conservatism in the Iraq Stock Exchange represented by the commercial banks (Al-Khaleeji Commercial Bank, Al-Mansour Investment Bank, Development Investment Bank, Iraqi Middle East Investment Bank, Sumer Commercial Bank, Ashur International Investment Bank) where the problem was The research is there an effect of applying the principles of governance on accounting conservatism, and a questionnaire was used to collect data, and the research tool included (33) paragraphs, and (92) questionnaires were distributed through personal e-mails (58) questionnaires through personal interviews, where a sample was formed Research from (120) employees working in the banking sector. The results were analyzed using the statistical program (spss), with a correlation relationship attributed to the application of governance principles to accounting conservatism. The research hypotheses were tested using (Kolmogorov-Smirnov K-S) program, and accounting conservatism was measured by using the (BTM) model through actual data. For the published financial reports, through the use of a measure of the book value of property rights to the market value of property rights, and the research ended with the most important conclusions and recommendations, which are that Iraqi banks are committed to applying the principles of governance, and that there is a correlation relationship attributed to it between the application of Iraqi banks to the principles of governance and the level of accounting conservatism. Determine the relative importance of the principles of governance on the practices of accounting conservatism